Effect of river water and groundwater pH quality to the teeth calcium level solubility in Kereng Bangkirai area, Central Kalimantan Province: Pengaruh kualitas pH air sungai dan air tanah terhadap kelarutan kadar kalsium gigi di daerah Kereng Bangkirai, Provinsi Kalimantan Tengah - Helena Jelita; Sintha Nugrahini (Makassar Dental Journal PDGI Makassar, 2021)
Background: Communities along the river in the Kereng Bangkirai area use river and groundwater (wells) for daily needs such as cooking and cleaning themselves and for other needs. It is important to know the quality of the water used by the people in the area, especially related to health conditions regarding the to the levels of dental calcium dissolved. Purpose: This study was aimed to prove the effect of pH quality dental calcium levels dissolved in river and groundwater from Kereng Bangkirai area. Method: This laboratory experiment with a control time series design was using groundwater, river water, aquadest and 36 per-manent human premolars with special criteria. The teeth were soaked for 5, 10, 15, 30, 45, 60 minutes and then measured the level of calcium solubility using a UV-vis spectrophotometer, then the average of dissolved calcium levels in the water was mea-sured. Result: Acidity of aquadest, groundwater and river water were 7.0, 4.08, and 3.16, consecutively; showed that the river water has a high level of pH. The average value of calcium solubility of aquadest was 3,534, in groundwater was 12,682 and the highest 17,882 in river water. Conclusion: Acidity level of river water and groundwater from Kereng Bangkirai area may affect calcium solubility of teeth.